Main nursing diagnoses in a patient with traumatic injury of the spinal cord from the perspective of high complexity - Oliveira, Ane Raquel de; Ribeiro, Wanderson Alves; Constantino, Gabriel Nivaldo Brito; Santos, Larissa Christiny Amorim dos; Guedes, Miriam Maria Ferreira; Souza, Érica Motta Moreira de; Reis, Elcio Gomes dos (Brazilian Journal of Science, 2024)
Traumatic spinal cord injury and sequelae are catastrophic events that adversely affect the victim’s functional capacity, and rapid rehabilitation is necessary. Nursing patients with spinal cord injury is essential for the patient’s rehabilitation. Nursing professionals offer individualized support according to different levels of complexity to prevent and treat the main complications caused by spinal cord injury. The objective of this study was to verify knowledge about the care of patients with spinal cord injuries undergoing rehabilitation. This study was developed from the virtual databases resident in the Library Research Portal: Latin American and Caribbean Literature in Health Sciences (LILACS); Scientific Electronic Library online (SciELO); Medical Literature Analysis and Retrieval System Online (MEDLINE) and Elsevier. It is concluded that nurses have knowledge of methods and scientific support to care for patients with spinal cord injuries. Their professional qualification provides greater technical competence in activities carried out with victims and facilitates the progression of trauma. Its process has a high contribution to rehabilitation, aiming at care that pays attention to each individual’s needs and particularities, helping to face the physical, social and psychological limitations of patients with traumatic spinal cord injuries.